2008
DOI: 10.1167/iovs.08-1849
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Deposits Lead to Retinal Degeneration in a Mouse Model of Alzheimer Disease

Abstract: Amyloid-beta deposits accumulate with age in the retina of a transgenic mouse model of AD. The amyloid-beta loads are accompanied by increased immunoreactivity for MCP-1, F4/80, and TUNEL-positive profiles in the RGC layer. The results suggest that amyloid-beta causes neurodegeneration in the retina of the doubly mutant transgenic mouse model of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
275
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(305 citation statements)
references
References 52 publications
27
275
1
2
Order By: Relevance
“…By analogy, the lack of human APP transgene expression in the periphery in APP23 mice may be responsible for the failure of ␤-amyloid induction after peripheral inoculations. Although this possibility cannot be ruled out, the absence of amyloid induction after intraocular and intranasal administration argues against it, because both the retina and the olfactory bulb, as components of the CNS, express the human APP protein in APP transgenic mice using neuronal promoters (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…By analogy, the lack of human APP transgene expression in the periphery in APP23 mice may be responsible for the failure of ␤-amyloid induction after peripheral inoculations. Although this possibility cannot be ruled out, the absence of amyloid induction after intraocular and intranasal administration argues against it, because both the retina and the olfactory bulb, as components of the CNS, express the human APP protein in APP transgenic mice using neuronal promoters (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Double transgenic mouse models have supported these findings, with RGCs undergoing apoptosis and APP deposition occurring in the GCL and inner nuclear layer. 101 Other studies of human tau transgenic mice 79 have reported accumulations of hyperphosphorylated transgenic tau in the RNFL and RGCs. Other transgenic mice models have suggested that the inner plexiform layer may be a more sensitive biomarker for detecting AD-related changes compared with RGCs, 70,80 making it difficult to draw firm conclusions.…”
Section: The Ganglion Cell Layer In Admentioning
confidence: 99%
“…The neuropathological hallmarks have been confirmed in the retina using transgenic mouse models of AD. Whole mount retinae of transgenic mice have demonstrated beta-amyloid structures in the retina (Ning et al 2008;Liu et al 2009;Peterz et al 2009) 32 . Histological examination of the retinal cross sections reveals elevated amyloid plaques in the RGCs, RNFL and superficial retinal layers (Ning et al 2008;Peterz et al 2009) 33 .…”
Section: Studies In Animal Modelsmentioning
confidence: 99%
“…Whole mount retinae of transgenic mice have demonstrated beta-amyloid structures in the retina (Ning et al 2008;Liu et al 2009;Peterz et al 2009) 32 . Histological examination of the retinal cross sections reveals elevated amyloid plaques in the RGCs, RNFL and superficial retinal layers (Ning et al 2008;Peterz et al 2009) 33 . Using retinal imaging techniques, plaque formation and clearance following immunotherapy, in which altered myelin antigen is loaded on dendritic cells, can be used in vivo and can be used to demonstrate the progress of the disease.…”
Section: Studies In Animal Modelsmentioning
confidence: 99%